Subjective Well-being of Special Education Teachers in China: The Relation of Social Support and Self-Efficacy - Fu, Wangqian; Wang, Lihong; He, Xiaohan; Chen, Huixing; He, Jiping (Frontiers in Psychology, 2022)
In order to explore the relationship of social support, self-efficacy and subjective well-being of special education teachers in China, 496 teachers from 67 special education schools were surveyed by questionnaire. We found that (1) the subjective well-being of special education teachers in China was in the medial level. (2) There were significant differences in subjective well-being level among teachers of different genders, teacher position, education background and teaching age. Male teachers were of higher subjective well-being; head teachers’ subjective well-being was lower than those were not head teachers; teachers with the educational background of postgraduate were of higher relaxation and tension than those with junior college educational background; the control scores of emotion and behavior of teachers with teaching age of 3 years and below were significantly lower than those of teachers with teaching age of more than 10 years. (3) Self-efficacy played a partially mediating role in the relationship between social support and subjective well-being of special education teachers. Suggestions to improve special education teachers’ subjective well-being was discussed in the paper.